Functionalized Zn/Al N-doped carbon nanocomposites with tunable morphology: Synergistic ultrafast low-temperature synthesis and tetracycline adsorption - Cao, Mengbo; Liu, Xun; Wang, Wei; Gao, Ming; Li, Yongsheng; Yang, Hongbing (Separation and purification technology, 2022)
[Display omitted] •Fabrication of mixed-metal composites via combustion reaction under low temperature.•Promotion influence of fuel type on physicochemical properties of sample.•Combustion reaction can provide inspiration for the time-saving preparation (0–10 s).•The adsorbents prepared in study have excellent adsorption capacity (>336 mg/g).•The adsorption capacity was enhanced by 32.5 % in 10 mg/L humic acid solution. The fast and efficient combustion technology was used to design zinc/alumina oxide N-doped carbon nanocomposites (Zn/Al-NCs) with assorted structures as pollutants adsorbent for capturing tetracycline (TC). XRD, SEM, TEM, EDX mapping, BET, and FTIR analysis techniques demonstrated the morphology and physicochemical properties of Zn/Al-NCs synthesized under mild conditions. The experimental results show that the pseudo-second-order kinetic and Langmuir model described the adsorption process well, indicating chemisorption and a monolayer adsorption nature. All Zn/Al-NCs exhibits excellent adsorption performance (>336 mg/g) to TC and the presence of humic acid (10 mg/L) made the adsorption capacity achieved a huge increasement (>446 mg/g) by forming a bridge bond. The adsorption mechanisms were pore-filling, electrostatic interactions, complexation, and H-bonds, confirming by BET, zeta potential, XPS, and FT-IR. The proposed synthesis strategy provides an efficient, excellent versatility, and time-saving way for preparing potential and high-performance materials for adsorbents.